(untitled) (Herald of Journalism, 2023)
Storytelling is one of the most popular video formats today; it is widely used by all media, but the continued growth of interest in video platforms leads to its increasing and transformation. The aim of the scientific work is to show the place of TV projects in the format of storytelling on the TV channels of Kazakhstan; to explore its relevance among the audience; to consider the mechanisms of creative search for the most attractive programs for the viewers. The scientific and practical significance of the work lies in the fact that, although the audience shows an increased interest in TV storytelling, its use and successful creation has its own requirements. News services use storytelling as a way to present information and journalists as a form. Video materials from Kazakhstani TV networks’ newscasts and journalistic television programs are examined as the part of the study. The study’s findings support the idea that the emotional impact of television content is most strongly felt when the audience empathizes with the characters through their stories. To transmit such feelings effectively, the project’s dramaturgy must be distinctive. Priority is paid to the visual quality in order to improve the effect of these aspects on television. Within the context of the study, attention was given to the works of scientists from Kazakhstan and abroad, many of whom concur that storytelling is a tried-and-true strategy in the media. Yet, TV programs in this genre have started to take precedence due to the rising interest in web storytelling. About 20 films were examined as the part of the study, and as a result, it can be said that the use of TV storytelling signals new developments in television journalism and the expansion of journalistic approaches in this direction. Keywords: storytelling, dynamics, journalism, empathy, emotion.